Experimental and numerical investigation of a CO2 heat pump system for electrical vehicle with series gas cooler configuration. (April 2019) - Wang, Yufeng; Wang, Dandong; Yu, Binbin; Shi, Junye; Chen, Jiangping
Highlights: Performance of a novel CO2 heat pump system with Series Gas Cooler (SGC) has been experimentally tested in both Air Conditioning (AC) and Heat Pump (HP) mode. A numerical model of CO2 SGC HP system has been established and validated with experiment results. The impacts of ambient temperature, discharge pressure and degree of superheat (DSH) on the HP system has been studied using the numerical model. A comparison between conventional CO2 system and SGC HP system is carried out based on the model. Abstract: The present study aims to investigate the performance a novel CO2 heat pump system designed for electrical vehicle with Series Gas Cooler (SGC) configuration. A numerical model is developed, and experiments in both Air Conditioning (AC) and Heat Pump (HP) mode are performed to validate this model. Based on the validated model, the impacts of ambient temperature, discharge pressure and degree of superheat on the system are discussed. Additionally, a comparison between conventional CO2 system and the novel SGC heat pump system is carried out using the developed model. The model can predict system capacity and COP with average errors of 5.1% and 6.0% in AC mode, and average errors of 7.2% and 5.8% are achieved in HP mode. The introduction of SGC into the heat pump system can bring an average increase by 33.7% for the system heating capacity, and an average increase by 35% is achieved for the system COP.